A quantitative model of relation between respiratory-related blood pressure fluctuations and the respiratory sinus arrhythmia. - Buchner, Teodor (Medical & Biological Engineering & Computing, 2019)
In order to propose an interpretation of recent experimental findings concerning short-term variability of arterial blood pressure (ABP), heart rate variability (HRV), and their dependence on body posture, we develop a qualitative dynamical model of the short-term cardiovascular variability at respiratory frequency (HF). It shows the respiratory-related blood pressure fluctuations in relation to the respiratory sinus arrhythmia (RSA). Results of the model-based analysis show that the observed phenomena may be interpreted as buffering of the respiratory-related ABP fluctuations by heart rate (HR) fluctuations, i.e., the respiratory sinus arrhythmia. A paradoxical enhancement (PE) of the fluctuations of the ABP in supine position, that was found in experiment, is explained on the ground of the model, as an ineffectiveness of control caused by the prolonged phase shift between the the peak of modulation of the pulmonary flow and the onset of stimulation of the heart. Such phasic changes were indeed observed in some other experimental conditions. Up to now, no other theoretical or physiological explanation of the PE effect exists, whereas further experiments were not performed due to technical problems. Better understanding of the short-term dynamics of blood pressure may improve medical diagnosis in cardiology and diseases which alter the functional state of the autonomous nervous system. Graphical Abstract A simple mathematical model of cardiorespiratory dynamics. A novel class of mathematical models of blood pressure dynamics in humans allows to represent respiratory modulation of Arterial Blood Pressure. The model shows how the phase shift in neural control of the heart rate may produce Paradoxic Enhancement of respiratory Blood Pressure fluctuations. Observed in experiment. The model has many options for further development.